Effective treatments for enhancing carbon fiber/epoxy interfacial properties and carbon yarn weavability. Issue 21 (November 2021) - Yao, Lan; Ruan, Xinyi; Hong, Shiting; Yang, Jiahua; Fan, Xiujun; Lin, Huoyue; Sun, Shiyuan; Zheng, Xianhong; Tang, Huarong; Qiu, Yiping
Carbon fiber-reinforced polymer composites have wide applications in the automotive, aerospace and construction industries, etc. However, due to the chemically inert surface of carbon fiber, interfacial problems always exist when the carbon fiber is infiltrated by the resin. In this study, polypyrrole (PPy) and carbon nanotubes (CNTs) were deposited on the carbon fiber surface in order to improve the interfacial properties between the carbon fiber and epoxy resin. After treatment, the interfacial shear strength increased as high as 55.7%, which was verified by microstructure characterization, including scanning electron microscopy, X-ray photoelectron spectroscopy and atomic force microscopy. In addition, PPy and CNTs were added to the epoxy sizing agent to strengthen the weavability of carbon yarns. The results showed that the abrasion resistance of the sized carbon yarns was significantly improved, and the fuzz weights were reduced.